Therapeutic Drug Monitoring of Vancomycin Following Critical Care Illnesses: Peak Concentration Determination Maybe Critical - Bita Shahrami; Farhad Najmeddin; Sarah Mousavi; Arezoo Ahmadi; Mojtaba Mojtahedzadeh (Research Center for Rational Use of Drugs (RCRUD), 2015)
#No Abstract#